Exploring the impact of vitamin D-related genetic variants on muscular fitness changes in middle-aged and older adults in Kosovo - Krasniqi, Ermira; Boshnjaku, Arben; Wagner, Karl-Heinz; Wessner, Barbara (Frontiers in Public Health, 2025)
IntroductionAge-related decline in muscle strength and performance significantly impact morbidity and mortality. Various factors including genetics have been investigated to better understand this decline. This study aimed to investigate longitudinal changes in physical performance and strength and their association with genetic variants in genes involved in the vitamin D pathway.MethodsThis longitudinal study was conducted in the Prishtina region, Kosovo, with community-dwelling adults over 40 years of age. Genomic DNA was extracted from saliva samples to assess single nucleotide polymorphisms in the vitamin D receptor (VDR) gene (rs7975232, rs2228570, rs731236, also referred to as ApaI, FokI, and TaqI, respectively) and the vitamin D binding protein (GC) gene (rs4588, rs2282679). Physical performance was assessed by isometric handgrip strength, 30-s chair stand, timed up and go and 6-min walk test. Vitamin D levels were assessed from blood samples only at follow-up.ResultsA total of 138 participants (65.1 ± 9.0 years, 52.2% female) were included. Over a 2.7-year period, significant declines in the 30-s chair stand test (p < 0.001) and timed up and go performance (p < 0.001) were observed, whereas BMI increased. Only female participants experienced a decrease in handgrip strength (p < 0.001). Genotyping showed significant associations of the ApaI variant with changes in BMI and handgrip strength. Participants with the minor CC genotype showed a greater increase in BMI and a greater decrease in absolute and relative handgrip strength. No significant interactions were observed for FokI and TaqI in the VDR gene, or rs4588 and rs2282679 in the GC gene. Vitamin D deficiency (<50 nmol/L) was prevalent in 47.5% of participants, with significant differences in 25(OH)D levels observed between genotypes of the GC gene (rs4588, p = 0.039; rs2282679, p = 0.036).ConclusionPhysical fitness declined significantly over time, with female participants experiencing a greater decline in handgrip strength. The ApaI variant in the VDR gene was associated with changes in muscle strength, while variants in the GC gene were associated with vitamin D levels. These findings suggest that genetic factors related to the vitamin D pathway may contribute to the age-related decline in muscle strength. Therefore, genetic predisposition should be considered when developing individual interventions for healthy aging.